Taylor's Cardiovascular Diseases A Handbook - Taylor, Robert B. (Springer New York : Imprint: Springer, 2005)
This handbook addresses the intricacies of providing cardiovascular care and consists of selected chapters from Family Medicine: Principles and Practice, Sixth Edition, the critically acclaimed and widely used reference for family physicians edited by Robert B. Taylor, MD. Internationally recognized contributors examine how to provide high-quality, ongoing care for common cardiovascular problems based on current evidence and time-tested methods in clinical practice. Chapters cover diseases of the heart and blood vessels that primary care physicians often find difficult to diagnose or treat, such as hypertension, ischemic heart disease, dyslipidemia, and venous thromboembolism. Other topics include cerebrovascular disease, cardiovascular emergencies, and medical care of the surgical patient. With a convenient, pocket-sized trim, this book is an indispensable resource for family physicians and others who provide primary care.